Comparing different sperm concentrations for optimizing cooled semen use in the dog - Sugai, Nicole; Werre, Stephen; Cecere, Julie T.; Balogh, Orsolya (Frontiers in Veterinary Science, 2024)
The use of shipping canine semen for artificial insemination has bloomed over the last twenty years. This allows for the spread of genetic material while overcoming geographical or timerelated challenges. Optimal sperm concentration for cooled semen transport in the dog is unknown. Often canine semen is extended 1:3-5 vol:vol without standardized sperm concentrations for cooled shipment. We compared different sperm concentrations for cooled storage and hypothesized that lower concentrations would result in better semen quality. Semen was collected from healthy client-owned dogs (n=8). Individual ejaculates were divided into a control aliquot (CON) extended 1:3 vol:vol with commercial extender. The remaining sample was centrifuged and extended to 200 x10 6 sperm/ml (C200), then serially diluted to 100, 50, and 25 x10 6 sperm/ml concentrations (C100-C25). Aliquots were cooled for 24h, then centrifuged and re-extended. Sperm concentration, plasma membrane integrity (PMI, %), motility (subjective total, STM; CASA total and progressive, TM, PM; %), and normal morphology (NM, %) were assessed in raw semen (T0), post-extension (T1), after 24h of cooling (T2), and after processing at 24h (T3). Cooling resulted in significant declines in STM and NM for all groups, and in decreased PMI for CON and C25-50. After cooling (at T2), PMI was significantly lower for C25 compared to all groups, and higher for CON compared to C25-100 (P≤0.038). Processing and reextension after cooling further decreased the spermiogram parameters. At T3, PMI for CON was similar to C200 but significantly higher than C25-100, while C25 had the lowest PMI. For motility parameters and NM, C25 performed worse than all or most of the other groups.Comparing CON at T3 with C25-200 at T2, PMI, STM and NM for CON were significantly lower than C25-200, C200, and C100-200, respectively. In conclusion, our results show that cooling canine semen for 24h at 200 x10 6 sperm/ml final concentration after processing, or extending 1:3 vol:vol without centrifugation is preferred based on highest PMI. If volume restrictions apply, processing raw semen and extending to the desired volume with higher sperm concentrations at the collection facility is superior to centrifugation and volume adjustment after 24h of cooled storage.